Extending the notion of customer value to surfing camps. Issue 8 (August 2021) - Wilson, Brad; Rita, Paulo; Barrios, Andres; Popp, Bastian
Abstract: This study applies the germane principles of service-dominant logic by investigating how different dimensions of service value impact customers' satisfaction and related behavioral intentions in the surf camps context. An empirical model was developed and tested via survey responses from 300 Portuguese surf camps tourists who profiled their experience. Data were analyzed using Structural Equation Modeling, specifically Partial Least Squares (PLS-PM). Results highlight the respective impact the numerous value dimensions (functional, emotional, social, epistemic, experiential, and contextual) have on the overall level of perceived value as well as its resultant impact on satisfaction and repurchase intentions. Abstract : Customer value; Service-dominant logic; Surf camps; Tourism marketing.